Collusion strategies of container shipping chain under supervision based on tripartite evolutionary game - Liu, Zongtuan; Xu, Ying; Gao, Yuchao; Li, Yan (Frontiers in Physics, 2025)
As over 80% of global trade relies on maritime transport, and container shipping accounts for more than 90% of the total value of maritime trade. The research on collusion strategies in a monitored container transport chain based on a tripartite evolutionary game, which this paper tackles, is a very interesting topic as an application of game theory. In today’s world where global supply chains are becoming more complex, understanding the strategic interactions between the parties involved in container transport (shippers, carriers, port operators, etc.) is an essential task for improving logistics efficiency and realizing a fair competitive environment. This study investigates the strategic interactions among container terminals, liner enterprises, and Port Authorities under regulatory supervision, revealing two critical regimes. Firstly, when fines fall below regulatory costs, collusion persists despite lax supervision, stabilizing the system at a suboptimal equilibrium regardless of penalty-subsidy combinations. Secondly, when fines exceed costs, an evolutionary stable strategy (ESS) emerges if the total penalty-subsidy value undercuts collusion profits; otherwise, cyclical instability occurs as regulators oscillate between enforcement and relaxation due to fiscal constraints. Numerical simulations validate these dynamics, demonstrating how cost-profit thresholds govern strategic outcomes. Using a tripartite evolutionary game model and numerical simulations, we demonstrate how cost-profit thresholds govern these strategic outcomes. Our findings highlight the necessity of designing penalty structures that simultaneously ensure regulatory cost recovery and neutralize collusion incentives, providing actionable insights for maritime policymakers to balance deterrence effectiveness with enforcement sustainability in container shipping markets.